Design with operational amplifiers and analog integrated circuits - Franco, Sergio ([S.l.] : McGraw-Hill Science/Engineering/Math, 2001)
Franco's "Design with Operational Amplifiers and Analog Integrated Circuits, 3e" is intended for a design-oriented course in applications with operational amplifiers and analog ICs. It also serves as a comprehensive reference for practicing engineers. This new edition includes enhanced pedagogy (additional problems, more in-depth coverage of negative feedback, more effective layout), updated technology (current-feedback and folded-cascode amplifiers, and low-voltage amplifiers), and increased topical coverage (current-feedback amplifiers, switching regulators and phase-locked loops).
International Edition.